Design of electric motor drives with high fault-tolerant capability for aerospace applications - Wang, Isaac Xuanyuan (Nanyang Technological University, 2024)
This thesis investigates the performance of a novel Vernier machine, the Dual Permanent Magnet Hybrid-Slot Field Twisting Vernier Machine (DPM-HSFTVM), for aerospace applications. The study focuses on improving power efficiency and reducing vibration compared to traditional motors. Simulation result highlights significant improvements in efficiency and stability with the new design being 15% more efficient in terms of torque output as well as a 0.3 increase in power factor when comparing to the conventional design. These findings suggest the DPM-HSFTVM is well-suited for addressing the challenges of aerospace motor design.